Masonry infilled reinforced concrete frames with openings - Asteris, Panagiotis G.; Giannopoulos, Ioannis P.; Smyrou, Eleni E.; Chrysostomou, Christis (My University, 2011)
This work presents an assessment of the behavior of infilled frames. The feasibility of possible immediate implementation of some recent developments both in analysis and design of infilled frames for practical design is investigated. It is now widely recognised that masonry infill panels, used in reinforced concrete (R/C) frame structures, significantly enhance both the stiffness and the strength of the surrounding frame. However, their contribution is often not taken into account because of the lack of knowledge of the composite behaviour of the surrounding frame and the infill panel. Currently, Seismic Design Guidelines (EC8 - Part 3, FEMA - 440, ASCE 41-06) contain provisions for the calculation of the stiffness of solid infilled frames mainly by modeling infill walls as "diagonal struts." However, such provisions are not provided for infilled frames with openings. The present study, based on available finite element results, proposes analytical equations for obtaining the reduction factor, which is the ratio of the effective width of a diagonal strut representing a wall with an opening over that of the solid RC infilled frame. That will allow the calculation of the initial lateral stiffness of infills when an opening is present. The validity of the proposed equations is demonstrated by comparing our results, against work done by various researchers.
Keywords: Finite element method; Earthquake resistant design; Structural frames; Masonry